Leptospirosis and occupational exposure: a study in the city of Santa Cruz do Sul/RS - Marthina Alice Gressler; Rafaela Scheid; Débora Martins; Luciana Fanfa; Suzane Beatriz Frantz Krug (Revista de Epidemiologia e Controle de Infecção, 2012)
Background and Objectives: The study is justifi ed by the high number of cases of leptospirosis in the studied city, with an incidence of 29 cases per 100,000 inhabitants in Santa Cruz do Sul and 4.5 cases per 100,000 inhabitants in the state of Rio Grande do Sul. The aim of this study was quantify the occupational cases of leptospirosis and establish a profile of individuals who acquired leptospirosis due to this type of exposure in the workplace in Santa Cruz do Sul / RS. Methods: This is a documentary study, of which retrospective data were collected on the Leptospirosis Notifi cation Forms of the System for Notifi able Diseases (Sinan), from January 2000 to December 2010. Results: There were 350 cases of leptospirosis in Santa Cruz do Sul in 10 years, 118 (33,7%) were work-related, and of these, 93% were male cases. The most affected age groups were between 20 and 29 years and between 40 and 49, both with 28 cases. Regarding occupation, 86 (72,9%) of the 118 workers were farmers. Conclusion: Work-related Leptospirosis affects mainly men of working age whose professions show greater exposure to its agent. It is known that, as this is an endemic disease, the eradication of leptospirosis is unlikely. However, the number of cases can be reduced by preventions measures most effective. KEYWORDS: occupational health. leptospirosis. occupational exposure